Gaya Bercerita Unik di Akun Youtube @hippiearab: Menyatukan Agama dan Keseharian - Ichfani Nurtania Zahra (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Employing a qualitative methodology that integrated video content analysis and interviews with both the curator and viewers of the YouTube channel @hippiearab, this research aims to elucidate the distinctive narrative approach utilized in the propagation of religious tenets. The central discovery of this inquiry highlights that a direct, relatable to daily life, and captivating storytelling mode simplifies the comprehension of religious doctrines for the audience. Furthermore, the application of everyday language within the content has demonstrated its efficacy in forging a robust emotional bond between the content creator and the video recipients. This study underscores the pivotal role of online media, notably YouTube, as an influential tool for instilling spiritual values in younger generations within the context of their ordinary existence.